ANALISIS MOLEKULER TANAMAN FUNGSIONAL GENUS Momordica BERDASARKAN DNA BARCODE REGION matK - Sumarlina Sumarlina; Tia Sofiani Napitupulu; Aulia Nadhirah; Fadli Mulyadi (JURNAL AGRIMENT, 2023)
Most of the plant species from the genus Momordica which originated from Asia and Africa have been shown to have functional value, both as food and medicinal plants. However, the quality of utilization of medicinal plants needs to be controlled through accurate authentication, for example through molecular analysis based on DNA barcodes. The matK sequence is one of the most widely used DNA barcode regions in plant molecular studies. Therefore, this study was conducted to determine the genetic variation and phylogenetic relationships of several taxa from the genus Momordica, as well as to analyze the effectiveness of the application of the matK gene as a barcode region in the genus Momordica. The study was conducted by collecting matK sequence data from NCBI in order to obtain sequence data from 12 taxa of the genus Momordica. The data were then aligned and analyzed using MEGA 11 software which included analysis of genetic variation, reconstruction of phylogenetic trees based on Maximum Parsimony, and calculation of genetic distance values using the Kimura-2-Parameter substitution model. The results showed that the molecular analysis of 12 taxa from the genus Momordica based on matK DNA barcode region had been successfully carried out, as evidenced by the successful reconstruction of the phylogenetic tree which showed clear separation both at the interspecies and intraspecies levels. However, the separation that has formed has not been able to show the grouping of taxa based on the origin. Likewise with the calculation of genetic distance values which show consistent results. All analyzes also showed that the matK DNA barcode region has a sequence composition that is quite effective for molecular analysis for genus Momordica, but further studies are required to improve the effectiveness and accuracy of the results provided